Driving after Upper or Lower Extremity Orthopaedic Surgery - MacKenzie, James S.; Bitzer, Alexander M.; Familiari, Filippo; Papalia, Rocco; McFarland, Edward G. (Joints, 2018)
Orthopaedic procedures can affect patients' ability to perform activities of daily living, such as driving automobiles or other vehicles that require coordinated use of the upper and lower extremities. Many variables affect the time needed before a patient can drive competently after undergoing orthopaedic surgery to the extremities. These variables include whether the patient underwent upper or lower extremity surgery, the country in which the patient resides, whether the right or left lower extremity is involved, whether the dominant arm is involved, whether the extremity is in a cast or brace, whether the patient has adequate strength to control the steering wheel, and whether the patient is taking pain medication. The type and complexity of the procedure also influence the speed of return of driving ability. Few studies provide definitive data on driving ability after upper or lower extremity surgery. Patients should be counseled not to drive until they can control the steering wheel and the pedals competently and can drive well enough to prevent further harm to themselves or to others. This review discusses the limited recommendations in the literature regarding driving motorized vehicles after upper or lower extremity orthopaedic surgery.
Keywords: driving; lower extremity; motorized vehicle; orthopaedic surgery; upper extremity